Workshops Report: Climate Resilient Rangelands in the Northern Territory of Australia - Sircely, Jason A; Hennig, J.; Penrose, B. (International Livestock Research Institute, 2025)
The 2025 XII International Rangeland Congress held in Adelaide, Australia, in June 2025 provided an opportunity for researchers from the International Livestock Research Institute (ILRI) and the University of Arizona (UAZ) to join Charles Darwin University (CDU) in holding workshops on Climate Resilient Rangelands in the Northern Territory of Australia. Three workshops were conducted, attended by commercial graziers, trade group representatives, government staff, and researchers from the Commonwealth Scientific and Industrial Research Organization (CSIRO) and other research institutions. The goals of the workshops were to present and discuss options for improving the climate resilience of rangeland livestock production in the tropical savannas and deserts of the Northern Territory, including lessons from Australia, Africa, and North America, engage in development of research concepts for future work in the Northern Territory and intercontinentally through collaboration, and to use lessons learned in Northern Territory that may be applicable in rangelands elsewhere globally.